The influence of intrinsic and extrinsic rewards on practical student perceive performance in their organization / Husna Mohd Saini and Nurul Hafizah Ahmad Zubir - Mohd Saini, Husna; Ahmad Zubir, Nurul Hafizah (Faculty of Business and Management, 2015)
Work performance becomes important for practical students when they doing their internship in their organizations. To engage in the practice of work performance of practical students, employers must understand the needs of practical students when doing their internship in the organizations. Performance of employee doing related activities expected of an employer and how well those activities were executed. Based on Afshan et al. (2012) define performance as the achievement of specific task measured against predetermined or identified standards such as accuracy and completeness. Thus, to make work performance effective, it’s reflecting on intrinsic and extrinsic rewards among practical students in their organizations. This research study on two dimensions that influence work performance which is intrinsic and extrinsic rewards. Intrinsic rewards are dividing by three items which are recognition, responsibility and learning opportunity. Whereby extrinsic rewards also dividing by three items which are compensations and benefits, career advancement and working condition. The researchers need to find out what the relationship with work performance is and which one of these factor that most significant to work performance among practical students in their organizations. Besides, researchers also want to determine the level of work performance among practical students in their organizations. This study has conducted through distributed the questionnaire to all practical students in Faculty Business Management using email. The finding of this study we can see the level of work performance of practical student is high because it have a positive relationship with intrinsic and extrinsic rewards. Thus, the most factors that influenced practical students work performance is extrinsic rewards which is working conditions.